Intragenic recombination and a chimeric outer membrane protein in the relapsing fever agent Borrelia hermsii. - Kitten, T (1993)
The spirochete Borrelia hermsii, a relapsing fever agent, evades the host's immune response through multiphasic antigenic variation. Antigen switching results from sequential expression of genes for serotype-specific outer membrane proteins known as variable major proteins (Vmp's); of the 25 serotypes that have been identified for the HS1 strain, serotypes 7 and 21 have been studied in greatest detail. In the present study, an atypical variant was predominant in the relapse from a serotype 21 infection in mice; relapse cells were bound by monoclonal antibodies specific for Vmp21 as well as antibodies specific for Vmp7. In Western blots (immunoblots), the variant had a single Vmp that was reactive with monoclonal antibodies representing both serotypes. The gene encoding this Vmp, vmp7/21, was cloned and characterized by restriction mapping and sequence analysis to determine the likely recombination event. Whereas the 5' end of vmp7/21 was identical to that of vmp21, its 3' end and flanking sequences were identical to the 3' end of vmp7. Unlike other vmp genes examined thus far, the vmp7/21 gene existed only in an expressed form; a silent, storage form of the gene was not detected. We conclude that the vmp7/21 gene was created by an intragenic recombination between the formerly expressed vmp21 gene and a silent vmp7 gene. This finding suggests that the lack of cross-reactivity between variants, which is usually observed, results from immunoselection against variants possessing chimeric Vmp's rather than from a switching mechanism that excludes partial gene replacements.